Cost Of Cultivation And Marketing Of Pepper In Idukki District - Vinod G (Department of Agricultural Economics, College of Horticulture, 1984)
This study was done in1983. Data for estimating the cost of cultivation were generated from a multi-stage random sample of 72 farmers stratified on the basis of the size of holding. The cost was analysed operationwise and inputwise. The economics of production was also studied by a capital productivity analysis. Pepper marketing was studied from the level of the producers to the terminal market at Cochin. The price spread was arrived at by the concurrent margin method. The annual cost of cultivation, per hectare, for the first seven years, were Rs.5952.54, Rs.3958.64, Rs.4150.55, Rs.4583.87, Rs.4901.45, Rs.5412.39 and Rs.5506.03 in that order, at the level of the aggregate sample. In general the most conspicuous cost creating operation was the cultural operation, while the corresponding input was human labour. Roughly one-fourth of the total cost was fixed and the rental value of land was predominant in this. The cost of cultivation was found to decrease as the size of holding increased, viewed on a unit area basis. The analysis of capital productivity revealed that, on the whole, investment in pepper cultivation had a pay-back period of 10 years, a benefit-cost ratio of 1.09, a net present worth of Rs.4180.76 and an internal rate of return of 13.48 per cent. The market structure, market practices and marketing costs were explored fairly in detail. The marketing channels identified were channel I: Producer- Village Merchant- Upcountry Wholesaler- (Commission Agent) – Exporter, channel II: Producer- Upcountry Wholesaler- (Commission Agent) - Exporter, channel III: Producer- Village Merchant- Upcountry Wholesaler- (Commission Agent) - Internal Wholesaler and channel IV: Producer- Upcountry Wholesaler- (Commission Agent) - Internal Wholesaler. The price spread in these four channels were found to be 13.94 per cent, 13.38 per cent, 11.20 per cent and 10.63 per cent in that order.